Efektivitas Penerapan Metode Demonstrasi di SMP Negeri 2 Gudo Jombang - Khoirunnisa, Ummul; Chotimah, Chusnul (JoEMS (Journal of Education and Management Studies), 2022)
The demonstration method is a teaching and learning method that is suitable for creating a conducive teaching and learning situation. This demonstration method is a learning method by demonstrating items, events, rules, and the sequence of activities, either directly or through the use of teaching media that are relevant to the subject or material presented. Methods This research uses a qualitative research approach. Data collection techniques in this study were observation, interviews and documentation. The results of this study indicate that the implementation of teaching and learning situations at SMP Negeri 2 Gudo, Jombang Regency is the result of questions generated from the formulation of the problem. The results of the problem formulation, namely the efforts of PAI teachers in implementing teaching and learning situations at SMP Negeri 2 Gudo, Jombang Regency were quite good. From here there are also advantages and disadvantages of implementing teaching and learning situations using the demonstration method and also the great results achieved from the application of teaching and learning situations with the demonstration method which are taken into consideration and benchmarks for future evaluation materials.